The relation between maternal locus of control and coping styles of pediatric leukemia patients during treatment - Concetta Polizzi; Giovanna Perricone; Valentina Fontana; Paolo D'Angelo; Momcilo Jankovic; Francesca Nichelli; Calogero Taormina; Sofia Burgio (MDPI AG, 2020)
The present study focuses on the relation between coping strategies of children with leukemia during treatment and locus of control of their mothers. In particular, the study aims to determine whether maternal locus of control can influence sick children's coping styles, and if this relation can be used to predict maladjustments. The study analyzed a cohort of 60 pediatric leukemia patients undergoing treatment and a group formed by their mothers. The participants were recruited from two Pediatric Onco- Hematology Units in Italy. The Child Behavioral Style Scale (CBSS) was used to assess children's coping strategies, whereas the Parental Health Locus of Control Scale (PHLCS) was employed to analyze maternal locus of control. A linear regression model was applied to verify a possible interdependent relationship between children's coping styles and maternal locus of control. The differences in mean CBSS scores were analyzed by K-S test. Multivariate analysis of variance was performed to assess any potential effect of child's gender, hospital context and maternal socio-cultural status on children's coping strategies. Our results show a significant relationship between children's coping strategies and maternal locus of control. In particular, the scales mass media, fate and healthcare professionals display a predictive effect on children's monitoring coping style, given the positive correlation observed (F=3.28, P=0.008). In contrast, the same scales negatively correlate with blunting coping style (F=3.5, P=0.005). Our results reveal several interesting resources having a profound impact on the psychological functioning of children with leukemia undergoing treatment as well as their mothers. Furthermore, with regard to the central hypothesis of the study, our findings show both positive and negative correlations between specific scales of maternal locus of control and children's coping style, which could be used to predict children at risk of emotional maladjustment.